2015
DOI: 10.1007/s12035-015-9538-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acetylcholine in the Inflammatory Response in Animals Surviving Sepsis Induced by Cecal Ligation and Puncture

Abstract: The cholinergic anti-inflammatory pathway controls the inflammatory response and nonreflexive consciousness through bidirectional communication between the brain and immune system. Moreover, brain acetylcholinesterase activity may have a role in regulating the vagus nerve in this pathway. Thus, we analyzed the role of acetylcholine (ACh) in the inflammatory response 15 days after induction of sepsis by cecal ligation and puncture (CLP). Balb/c mice were pretreated with or without donepezil (5 mg/kg/day, orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
1
21
0
1
Order By: Relevance
“…In addition, recent work from our group demonstrated that VAChT expression levels, which directly modulate the levels of acetylcholine release (44), control lung inflammation in mice (19). Also, Jeremias et al (45) showed that VAChT modulates levels of cytokines released in lung in a model of cecal ligation and punctureinduced sepsis. Moreover, increasing evidence indicates that activation of a7nAChR can be protective in a variety of inflammatory diseases including ALI (18,29,46).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, recent work from our group demonstrated that VAChT expression levels, which directly modulate the levels of acetylcholine release (44), control lung inflammation in mice (19). Also, Jeremias et al (45) showed that VAChT modulates levels of cytokines released in lung in a model of cecal ligation and punctureinduced sepsis. Moreover, increasing evidence indicates that activation of a7nAChR can be protective in a variety of inflammatory diseases including ALI (18,29,46).…”
Section: Discussionmentioning
confidence: 91%
“…Also, Jeremias et al . (45) showed that VAChT modulates levels of cytokines released in lung in a model of cecal ligation and puncture‐ induced sepsis. Moreover, increasing evidence indicates that activation of α7nAChR can be protective in a variety of inflammatory diseases including ALI (18, 29, 46).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of cytokines, such as IL-1β, TNF-α, and IL-6, have been observed in the brain parenchyma and cerebrospinal fluid after sepsis (Jeremias et al 2015 ; Takahashi et al 2014 ). The neuropathology in SAE is quite similar to that in patients with severe sepsis in terms of elevated levels of proinflammatory cytokines in the brain (Blom et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after the surgery, the mice were intraperitoneally injected Dex (50 μg/kg) or the same volume (200 μl) of vehicles PBS. After that, the mice were injected subcutaneously with 1 ml of sterile saline for resuscitation and put into an incubator until they recovered from the anaesthesia [19,20].…”
Section: Adenovirus Gene Deliverymentioning
confidence: 99%